Strategies and Challenges for Women Protection against Violence: A Case Study of Jakarta and Cairo - Nurul Adhha; Asep Saepudin Jahar; Kamarusdiana Kamarusdiana; Imam Subchi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
This study aims at illustrating the weakness of women protection against violence in various levels in Indonesia and Cairo. Both countries share common failure in protecting women due to the incapability poor performance of police and local governments. In addition, cultural values and religious understanding have played a part in narrowing the concern to the protection. Basically, Indonesia has already set some legal instruments to protect women against any violence through the gender-based laws and policies. In practice, however, such laws and policies have faced several complexities in regards to the nature of institution, security role and social values among society. Violence against women is generally regarded as moral and norm violations instead of criminal acts. In some respects, the weakness of law enforcement indicates the ineffectiveness of the existing laws and policies. Similarly, Egypt also suffers from the backwardness of women protection against violence. In fact, legal reform for women protection in this country was made in 2014 through special constitution. Such constitution is the first law set to promote the status and role of women in both private and public affairs. In addition, it also aims at ensuring equal rights and obligations in women protection which is free from discrimination and empowering as well as caring for women and girls victims at various stages of case handling system. Referring to the data and actual documents collected during the research, this study has found a result stating women protection has faced various aspects of social and political interests. To that end, it necessary to strengthen the role of civil society in controlling the government and making people aware of gender equality in particular and human rights in general.